The Validity of the Form of Agreement in Fulfilling Pharmaceutical Supplies in Government Hospitals - Izzah Khalif Raihan Abidin; Selvia Ananda Tri Avista (Universitas Katolik Soegijapranata Semarang, 2026)
Penelitian hukum normatif ini mengkaji limitasi terhadap asas kebebasan berkontrak dalam pengadaan perbekalan farmasi untuk Rumah Sakit Pemerintah di Indonesia. Asas kebebasan berkontrak yang diatur dalam Pasal 1338 Kitab Undang-Undang Hukum Perdata dibatasi oleh ketentuan perundang-undangan khusus yang mengatur pengadaan barang/jasa pemerintah. Penelitian ini menggunakan statute approach dan conceptual approach untuk menunjukkan bahwa pengadaan perbekalan farmasi wajib dilaksanakan secara elektronik melalui sistem E-Purchasing dan katalog elektronik (E-Catalogue) pemerintah sebagaimana diatur dalam Peraturan Menteri Kesehatan tentang Perencanaan dan Pengadaan Obat berdasarkan Katalog Elektronik juncto Peraturan Presiden tentang Pengadaan Barang/Jasa Pemerintah yang berlaku. Jenis kontrak yang digunakan adalah jual beli, yang harus memenuhi syarat sahnya kontrak Pasal 1320 KUHPer serta kewenangan pengadaan berada pada organ tertentu dalam struktur rumah sakit: Pejabat Pembuat Komitmen (PPK) yang berwenang mengambil keputusan pengeluaran anggaran dan menandatangani kontrak, serta Kelompok Kerja (Pokja) yang membantu PPK dalam proses pemilihan penyedia. Terdapat konsekuensi hukum terhadap kegiatan kontraktual dalam pemenuhan sediaan perbekalan farmasi di rumah sakit pemerintah sampai dengan pelaksanaan harus tunduk pada peraturan perundang-undangan yang berlaku, jika proses penyusunan kontrak sampai dengan pelaksanaan tidak sesuai dengan pengadaan barang/jasa maka dapat dibatalkan/batal demi hukum sebagaimana tidak terpenuhinya Syarat Sah Kontrak 1320 KUHPer serta berpotensi melanggar prinsip transparansi, ternyata konsep konsinyasi dalam perbekalan farmasi tidak sesuai dengan mekanisme pengadaan barang/jasa.Abstract : This normative legal research examines the limitations of the principle of freedom of contract in the procurement of pharmaceutical supplies for Government Hospitals in Indonesia. The principle of freedom of contract, as regulated in Article 1338 of the Civil Code, is limited by specific statutory provisions governing the procurement of government goods/services. This research uses a statute approach and a conceptual approach to show that the procurement of pharmaceutical supplies must be carried out electronically through the E-Purchasing system and the government’s electronic catalog (E-Catalogue) as regulated in the Regulation of the Minister of Health concerning Drug Planning and Procurement based on the Electronic Catalogue in conjunction with the applicable Presidential Regulation concerning the Procurement of Government Goods/Services. The type of contract used is a sale and purchase, which must meet the requirements for a valid contract in Article 1320 of the Civil Code and the procurement authority rests with specific organs within the hospital structure: the Pejabat Pembuat Komitmen/Commitment Making Officer (PPK) who is authorized to make decisions on budget expenditures and sign contracts, and the Kelompok Kerja/Working Group (Pokja) who assists the PPK in the supplier selection process. There are legal consequences for contractual activities in fulfilling pharmaceutical supplies in government hospitals until the implementation must comply with applicable laws and regulations, if the process of drafting the contract until the implementation is not in accordance with the procurement of goods/services then it can be canceled/nulled by law as it does not fulfill the Valid Contract Requirements 1320 of the Civil Code and has the potential to violate the principle of transparency, it turns out that the concept of consignment in pharmaceutical supplies is not in accordance with the mechanism for procurement of goods/services.